2013
DOI: 10.1364/oe.21.012249
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetically induced grating in asymmetric quantum wells via Fano interference

Abstract: We propose a scheme for obtaining an electromagnetically induced grating in an asymmetric semiconductor quantum well (QW) structure via Fano interference. In our structure, owing to Fano interference, the diffraction intensity of the grating, especially the first-order diffraction, can be significantly enhanced. The diffraction efficiency of the grating can be controlled efficiently by tuning the control field intensity, the interaction length, the coupling strength of tunneling, etc. This investigation may be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
59
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(59 citation statements)
references
References 38 publications
0
59
0
Order By: Relevance
“…The cascade-type biexciton system has already been examined by pump-probe17 and two-photon absorption experments30 and proposed for studying entanglement dynamics37. Similar artificial structures have also been used for tunneling induced transparency and related applications38394041.…”
Section: Resultsmentioning
confidence: 99%
“…The cascade-type biexciton system has already been examined by pump-probe17 and two-photon absorption experments30 and proposed for studying entanglement dynamics37. Similar artificial structures have also been used for tunneling induced transparency and related applications38394041.…”
Section: Resultsmentioning
confidence: 99%
“…EIG initially was proposed in a Λ-type threelevel atomic system [1], then experimentally demonstrated in cold and hot atomic media [2][3][4]. The great attention to EIG is due to its potential applications in significant fields such as all-optical switching and routing [2], probing material optical properties [4], atomic/molecular velocimetry [5], light storage [6,7], optical bistability realization [8], beam splitting and fanning [9], shaping a biphoton spectrum [10], developing novel photonic devices in semiconductor QW systems [11], and controlling multi-wave mixing signals via photonic band gap of electromagnetically induced absorption grating in atomic media [12]. It is shown that the intensity of higher-order diffractions could be enhanced in a three-level ladder type system [13].…”
Section: Introductionmentioning
confidence: 99%
“…While for EIT, the coherence depends on external-field coupling. TIT has been widely used for ultrafast switch [22], enhanced Kerr nonlinearity [23,24], optical grating [25], wavelength selection [26] and separating optical precursors [27]. Tunneling-coupled two adjacent QDs form a QD molecule (QDM) [28].…”
Section: Introductionmentioning
confidence: 99%